Quality of supervisor-subordinate relationship and work outcome: organizational justice as mediator - Hassan, Arif; Chandaran, Suresh (KENMS-IIUM Press, 2005)
The quality of the leader–member exchange relationship is conceptualized in the leader-member exchange (LMX) theory as a determinant of employees’ attitude and behavior. Likewise, organizational justice, which includes distributive and procedural justice, is recognized as an important determinant of employees’ commitment, atisfaction and other outcome variables. Although the LMX-work/organizational outcome relationship has attracted considerable research interest, the role of mediating variables such as organizational justice perception has not been well examined. This paper reports the findings of a study which investigates how the quality of supervisor-subordinate relationship determines employees’ distributive and procedural justice perception which in turn determines employees’ job satisfaction, organizational commitment and turnover intentions. It is expected that in a relationship oriented society like Malaysia, the quality of the dyadic relationship would strongly influence employees’ attitude and behavioral tendencies. Data are collected from one food processing, one pharmaceutical, and two manufacturing companies located in Malaysia. The sample consists of 154 executives, supervisors and middle-level managers who volunteer to participate in this study. The results support the hypothesis that distributive and procedural justice mediates the relationship of LMX with employees’ job satisfaction, organizational commitment and turnover intentions. Procedural justice is found to have full mediation effect in the LMX-outcome variables relationships. It was partial mediation in the case of distributive justice. The results suggest the importance of leader behavior and organizational justice in promoting job satisfaction and organizational commitment, and minimizing the turnover intentions of employees.